Move fast and break things! innovation-intensive strategy, organizational permissiveness, and corporate wrongdoing. Issue 2 (April 2023) - Grieser, William; Krause, Ryan; Li, Rachel; Priem, Richard; Simonov, Andrei
Abstract: With the revelation of questionably ethical practices at the world's most innovative firms, scholars and practitioners have begun to question whether a link might exist between innovation and wrongdoing. We introduce the concept of organizational permissiveness—i.e., tolerance of employees' norm-challenging behavior—to begin unpacking the relationships between cognitive norm-breaking, radical innovation, and corporate wrongdoing. We argue that organizational permissiveness partially mediates the effects of innovation-intensive strategy on innovation outcomes and multiple types of corporate wrongdoing. We analyze a sample of publicly held U.S. firms to demonstrate that the norm-breaking necessary for radical innovation also can produce corporate wrongdoing. Moreover, organizational permissiveness is a mechanism leading to both outcomes. We then use a smaller-sample quasi-experiment examining how merger and acquisition events affect individual scientists' patenting behavior. This provides further support for our hypothesized causal assertions.